Effect of Polypropylene Fibers on Moisture Susceptibility of Warm Mix Asphalt - Sura Fawzi Mohammed; Mohammed Qadir Ismael (Civil Engineering Journal, 2021)
Warm Mix Asphalt (WMA) is a modern energy-saving process that uses environmentally friendly materials, has lower mixing and compaction temperatures, and uses less energy and releases less contaminants than conventional hot mix asphalt. Moisture damage poses one of the main challenges of the material design in asphalt pavements. During its design life, the asphalt pavement is exposed to the effect of moisture from the surrounding environment. This research intends to investigate the role of the polypropylene fibres for modifying the moisture susceptibility for the WMA by using different percentages of polypropylene (namely 2, 4, and 6%) by weight of the binder of the control mixture (WMA). In this paper, the physical characteristics of the asphalt cement, Marshall properties, Tensile Strength Ratio (TSR) and Index of Retained Strength (IRS) were determined to establish the effect of the polypropylene on the moisture susceptibility of the WMA. The results displayed that the modification of the AC with polypropylene caused an increase in the optimum asphalt content by 1.03, 3.09, and 11.3%, with the addition of 2, 4 and 6% of the P.P., respectively. The moisture resistance of the asphalt mixture was enhanced by adding the P.P., according to the rise in the Tensile Strength Ratio (TSR) and Index of Retained Strength (IRS) values. The TSR value showed 9.4, 18.2 and 19.5% increase when the P.P. increased from 0.00 to 0.02, 0.04, and 0.06, respectively; besides, the IRS showed improvement with the addition of the P.P. to the WMA. Doi: 10.28991/cej-2021-03091704 Full Text: PDF